Icons and idols in Dante and Petrarch - Rushworth, J (Maney Publishing, 2016)
This essay explores the presence of a polarised thematic of icons and idols in the works of Dante and Petrarch. In Dante’s Vita nuova and Commedia, and in Petrarch’s Canzoniere and Latin letters, the Veronica – vera icon – of Christ is invoked in relation to the poet’s beloved either as an analogous model or as a point of opposition. In the latter case, which applies both to Dante’s siren (in Purgatorio XIX) and to Petrarch’s Laura (particularly in RVF 16), the presence of the Veronica can only properly be understood in contradistinction to the poetic idolatry which haunts each text. In particular, Laura is found to be an idol for three reasons: Petrarch’s worship of her name; doubts over her existence; and the Pygmalion myth that haunts Martini’s portrait of Petrarch’s beloved. For Petrarch, the only possible solution to the temptation of idolatry is a Dantean one, namely invocation of a further icon, the Virgin Mary (both in RVF 366 and in his Testament), even if the Canzoniere is never fully able to forsake Laura.